DEM-CFD-based simulation and optimization of a combined pneumatic-centrifugal wheat seed-metering device - Ma, Duanxu; Shi, Song; Li, Hui; Wei, Guojian; Zhou, Jilei; Shi, Yupeng; Liu, Hu (International Journal of Agricultural and Biological Engineering, 2025)
Pneumatic wheat seed-metering device often has a poor seed-filling state under the high-speed working condition, which adversely affects precision seeding. This paper describes a wheat seed-metering device that employs a combined mechanical–pneumatic seed-filling method. The orifice structure and seed-filling space at the nozzle are optimized to improve the seed-filling efficiency and seed-carrying stability. The working process of the wheat seed-metering device was analyzed, the principles of the seed-filling and seed-cleaning processes were elucidated, the factors influencing the seed-filling performance and seed-carrying stability were investigated, and the discrete element method–computational fluid dynamics (DEM-CFD) simulation method was employed to simulate the working process. The nozzle-orifice diameter, seed-filling-space angle, and rotation speed were determined as the simulation influence factors, and the trends of the nozzle void fraction, resistance to clearing, and initial dropping position were analyzed from a microscopic scale. On a macroscopic scale, the seed-leakage rate, reseeding rate, and grain-spacing qualification rate as performance-evaluation metrics were analyzed, and the significant order of impacts for these influencing factors and their interaction effects was obtained. Through secondary optimization experiments, the optimal parameter combination was determined to be a nozzle-orifice diameter of 1.7 mm, a seed-filling-space angle of 39.3°, and a rotation speed of 657.4 r/min. Static bench-validation tests and indoor vibration-environment simulation experiments were conducted, and the results were compared with a control group. The findings reveal that when the seed-metering plate rotation speed varies between 400 r/min and 1000 r/min, the optimized seed-metering plate exhibits a seed-leakage rate below 7.6% and superior performance in all indicators compared to the original seed-metering plate, indicating a significant improvement in seed-filling efficiency and seed-carrying stability. Keywords: wheat seed-metering device, pneumatic centrifuge, drag force, DEM-CFD DOI: 10.25165/j.ijabe.20251805.9438 Citation: Ma D X, Shi S, Li H, Wei G J, Zhou J L, Shi Y P, et al. DEM-CFD-based simulation and optimization of a combined pneumatic-centrifugal wheat seed-metering device. Int J Agric & Biol Eng, 2025; 18(5): 127–141.